Proceedings of International Conference on Muslim Society and Thought: Committee - Mahzumi, Fikri (Proceedings of International Conference on Muslim Society and Thought, 2019)
The 1st International Conference on Muslim Society and Thought “Muslim Society and Globalization” held by Ushuluddin and Philosophy Department of Sunan Ampel State Islamic University Surabaya, Indonesia and Fakulti Pengajian Islam Universiti Kebangsaan Malaysia.